ENFSI collaborative testing programme for fingermarks: Past experiences and future perspectives. (June 2017) - Mattei, A.; Fish, J.; Hilgert, M.; Lövby, T.; Svensson, M.; Vaughan, J.; Zampa, F.
Abstract: As early as 2004 the Fingerprint Working Group of the European Network of Forensic Science Institutes (ENFSI) has organised proficiency tests (PT's) as well as collaborative exercises (CE's) as a way of raising standards within the fingerprint profession. Participation in PT's and CE's is a key element in the ISO/IEC accreditation process as they enable laboratories to monitor the quality of their analytical results. On the basis of the European Council Framework Decision 2009/905/JHA, of 30 November 2009, on Accreditation of forensic service providers carrying out laboratory activities [1], from November 15th of 2015, only accredited laboratories are allowed to exchange fingerprint data with other EU countries. This article will provide an overview of the ENFSI collaborative tests for fingermarks in the fields of visualisation, imaging and individualisation. The characteristics of the testing programme are summarised, followed by an overview of the knowledge that has been gained, including lessons learnt. It is hoped that this reflective process can outline the critical issues that should be addressed as well as highlight future opportunities in relation to Monopoly Project 2013, " Proficiency Tests and Collaborative Exercises for the Fingerprint Domain ".